Future of Transport?- Future of Cities! - Bertolini, Luca (Promet - Traffic&Transportation, 2012)
The future of transport, whatever it will be, cannot be consideredseparately from that of cities. But what, where and whenis the city today? The ability to provide opportunities for humaninteraction is the essential reason for cities to exist. In thepre-industrial past this required high-density, compact urbanforms. Modem transport and communication techniques havehowever increasingly offered human beings ways of interactingat a distance. Physical proximity is no longer needed by manytypes of urban activities. As a result, cities have decentralised,as industry first, then residences and services have fled the diseconomiesof high-density agglomerations. For the future,some even predict the advent of an entirely diffuse, 'virtual' city.Actual evidence is at best mixed. Next to ongoing decentralisation,there are also signals that point in the opposite direction,as there are activities that show a tendency to physicallyconcentrate, underscoring a persistent need for physical humaninteraction. These activities include business and financial services,the emerging sectors of culture, entertainment and themedia, but also certain types of residences and of production.As a result, rather than decentralisation or concentration, contemporarycities show a complex combination of decentralisationand concentration.How will these contrasting movements shape the cities ofthe future? Are telecommunication technologies going to radicallyalter current trends? Or will the quest for sustainability dothis? And what will the role of transp01tation- as cause and effect-be? The diffuse urban-regional accessibility warranted bythe car and the inter-metropolitan connections provided by theaeroplane have been essential conditions for the urbanisationpatterns of the recent past. But will the car and the aeroplanealso be the transportation means of the cities of the future?